Lactate Dehydrogenase Inhibitors Suppress Borrelia burgdorferi Growth In Vitro - Adam Lynch; Patrick Pearson; Sergey N. Savinov; Andrew Y. Li; Stephen M. Rich (Pathogens, 2023)
Borrelia burgdorferi, the causative agent of Lyme disease, has a highly reduced genome and relies heavily on glycolysis for carbon metabolism. As such, established inhibitors of lactate dehydrogenase (LDH) were evaluated in cultures to determine the extent of their impacts on B. burgdorferi growth. Both racemic and enantiopure (AT-101) gossypol, as well as oxamate, galloflavin, and stiripentol, caused the dose-dependent suppression of B. burgdorferi growth in vitro. Racemic gossypol and AT-101 were shown to fully inhibit spirochetal growth at concentrations of 70.5 and 187.5 μM, respectively. Differences between racemic gossypol and AT-101 efficacy may indicate that the dextrorotatory enantiomer of gossypol is a more effective inhibitor of B. burgdorferi growth than the levorotatory enantiomer. As a whole, LDH inhibition appears to be a promising mechanism for suppressing Borrelia growth, particularly with bulky LDH inhibitors like gossypol.